2009
DOI: 10.1021/jp811317y
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Structural Properties of Various Solvated Metalated 3-Halo-1-azaallylic Anions

Abstract: Metalated 3-halo-1-azaallylic anions are important building blocks for the preparation of a wide variety of heterocyclic and highly functionalized compounds. A theoretical description of the structural properties of halogenated 1-azaallylic anions in vacuo and in tetrahydrofuran (THF) solution is presented to gain insight into their reactivity behavior. The configurational flexibility of fluorinated and chlorinated 1-azaallylic anions is examined, and it is shown that these anions have far less configurational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 70 publications
(132 reference statements)
0
10
0
Order By: Relevance
“…First, implicit solvation (THF, ε = 7.58) was modeled by means of Onsager and PCM single-point calculations on the B3LYP/6-31G* (vacuum) geometries; these dual-level calculations are denoted as B3LYP/6-31G* (Onsager)//B3LYP/6-31G* and B3LYP/6-31G* (PCM)//B3LYP/6-31G*. Van Speybroeck and co-workers have recently used the single-point correction approach to model bulk solvent effects on explicitly solvated lithiated α-aminophosphonates and lithiated imines . Onsager single-point calculations require specification of a radius ( a 0 ).…”
Section: Methodsmentioning
confidence: 99%
“…First, implicit solvation (THF, ε = 7.58) was modeled by means of Onsager and PCM single-point calculations on the B3LYP/6-31G* (vacuum) geometries; these dual-level calculations are denoted as B3LYP/6-31G* (Onsager)//B3LYP/6-31G* and B3LYP/6-31G* (PCM)//B3LYP/6-31G*. Van Speybroeck and co-workers have recently used the single-point correction approach to model bulk solvent effects on explicitly solvated lithiated α-aminophosphonates and lithiated imines . Onsager single-point calculations require specification of a radius ( a 0 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous reported theoretical calculations demonstrated that the lithiated 3-chloro-3-methyl-1-azaallylic anion 1a (M = Li, R 1 = i Pr, R 2 = C 6 H 5 , R 3 = Me) is present in a monosolvated monomeric Z -isomer form and should readily undergo transmetalation to the zincated Z -isomer 1b (M = ZnCl, R 1 = i Pr, R 2 = C 6 H 5 , R 3 = Me). , In order the verify these calculations and to use these new fundamental insights in stereoselective organic synthesis, anions 1a and 1b , derived from the N -isopropylimine 4a of α-chloropropiophenone, were reacted with aromatic aldehydes 5 (Table , Scheme ). N -Isopropyl-α-chloro imine 4a was prepared by condensation of α-chloropropiophenone with isopropylamine in the presence of titanium(IV) chloride .…”
Section: Resultsmentioning
confidence: 91%
“…Syn and anti transition state structures ( TS1- syn and TS1- anti , respectively) for the aldol reaction of azaallylic anions 1 and benzaldehyde 5a in the presence of a Li + cation (with one solvating THF molecule) are shown in Figure . In our previous work, , it was shown that transmetalation of lithiated azaallylic anions 1a to zincated anions 1b takes place with ease. Subsequently, azaallylic anions 1b are present as monomers and bear a ZnCl + cation; however, free lithium cations are also expected to interact with the benzaldehyde oxygen to which the negative charge will be transferred after the addition reaction.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The effect of the solvent, water, is modeled as the sum of two contributions (see Figure ): one resulting from the coordination of one or more water molecules to the transition state (X) and one originating from the bulk solvent effect. , The first contribution is the free energy of solvation in vacuo (Δ G sol vacuo ) and accounts for the effect of hydrogen bonds that can assist the radical addition reaction while the second contribution essentially takes into account the permanent dipole moment of the surrounding water molecules by placing the transition state in a dielectric continuum, resulting in a dielectric solvation energy (DSE). For the latter effect, single point energy calculations using the C-PCM model as implemented in Gaussian03 is used with Pauling radii for the solute. , Combination of both contributions allows us to calculate the coordination free energy in solution, Δ G sol cpcm , from the thermodynamic cycle that is depicted in Figure .…”
Section: Methodsmentioning
confidence: 99%